Intensitas Penilaian Formatif dalam Pembelajaran Kalkulus dengan Mengendalikan Kemampuan Awal Mahasiswa - Supardi U S (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2011)
The objective of the study was to know the effects of formative assessment intensity toward Calculus learning outcomes with controlling university students’ prior capacity. Research using experimental methods, and can be concluded from the finding, that with controlling university students’ prior capacity, the group was given formative assessment each subject matter got higher score on Calculus learning outcomes than the group was given conventional formative assessment. The result showed that there was formative assessment intensity has effect toward Calculus learning outcomes with controlling university students’ prior capacity. To improve the quality of Calculus learning outcomes, the lecturers were supposed to evaluate the university stuents’ the better using formative assessment intensity each subject matter.